2020
DOI: 10.1016/j.media.2019.101543
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating gyral bias in cortical tractography via asymmetric fiber orientation distributions

Abstract: Diffusion tractography in brain connectomics often involves tracing axonal trajectories across gray-white matter boundaries in gyral blades of complex cortical convolutions. To date, gyral bias is observed in most tractography algorithms with streamlines predominantly terminating at gyral crowns instead of sulcal banks. This work demonstrates that asymmetric fiber orientation distribution functions (AFODFs), computed via a multi-tissue global estimation framework, can mitigate the effects of gyral bias, enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 42 publications
(63 reference statements)
1
41
0
Order By: Relevance
“…Recently, Teillac et al (2017) proposed an extension on the spin-glass model to reduce the gyral bias, although their proposal alters the target fibre orientations close to the sulcal walls to allow streamlines to smoothly bend into the gyral walls rather than an explicit constraint on the streamline density. Wu et al (2020) also showed a reduction in the gyral bias by encouraging a smooth transition between the radial fibre orientation in the grey matter and the tangential orientation underneath using asymmetric fibre orientation distribution functions ( Bastiani et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Teillac et al (2017) proposed an extension on the spin-glass model to reduce the gyral bias, although their proposal alters the target fibre orientations close to the sulcal walls to allow streamlines to smoothly bend into the gyral walls rather than an explicit constraint on the streamline density. Wu et al (2020) also showed a reduction in the gyral bias by encouraging a smooth transition between the radial fibre orientation in the grey matter and the tangential orientation underneath using asymmetric fibre orientation distribution functions ( Bastiani et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are some researches that extend DKI in microstructural environments with orientation heterogeneity ( Ankele, 2019 , Huynh et al, 2019b , Ankele and Schultz, 2015 ) and show significantly higher consistency in quantifying microstructure than the conventional DKI in the presence of orientation heterogeneity. Recent works are available on modeling the effects of diffusion in curving structures ( Karayumak et al, 2018 , Bastiani et al, 2017 , Wu et al, 2020 , Lee et al, 2020 ). Diffusion measurements are antipodally symmetric which means the probabilities of displacement along x and − x are equal, while the distribution of fiber orientations within a voxel is not symmetric in general ( Karayumak et al, 2018 ).…”
Section: Signal Representationsmentioning
confidence: 99%
“…Different sub-voxel patterns such as crossing, fanning, and bending, cannot be distinguished if a voxel-wise model is fitted to the signal. Therefore, the spatial information from the neighboring voxels should be considered ( Bastiani et al, 2017 , Wu et al, 2020 )…”
Section: Signal Representationsmentioning
confidence: 99%
“…51 Gyral bias refers to the difficulty of tracing highly curved axonal trajectories across WM-GM boundaries in gyral blades, which can affect the performance of tractography algorithms. 116 Schilling and colleagues 117 investigated the impact of gyral bias by comparing tractography against myelin histology performed on a Rhesus macaque brain. This effect was evident for single-and multi-fiber implementations (tensor and CSD) of deterministic or probabilistic tractography, though the bias introduced in tensor-based tractography was larger than that in CSD-based tractography.…”
Section: Impact Of Microstructural Propertiesmentioning
confidence: 99%